URGENSI PENDIDIKAN TOLERANSI DALAM WAJAH PEMBELAJARAN SEBAGAI UPAYA MENINGKATKAN KUALITAS PENDIDIKAN - Ayu Suciartini, Ni Nyoman (LPM IHDN Denpasar, 2017)
Indonesia is experiencing social unrest because of the emergence of the behavior of racism and intolerance. Mass media social also become the most fertile ground the outbreak of the issue of the behavior of intolerance. Clear impact affect the condition of Indonesia today. All involved in the world of education is necessarily aware that the behavior of intolerance cannot happen. education must respect differences and spread the value of good character through education tolerance in the middle of the condition of multiculturalism become characteristic of Indonesia. The importance of good tolerance education in schools or in universities must be paid attention to education is lost gradually declines but. The world of education must be free of purely from the practice of intolerance. Education is the place grow any differences and foster mutual respect among the differences. Teachers or educators as the spearhead education has a special role in inculcating tolerance in the world of education will become an example to all it broadcasts.